2011
DOI: 10.1007/s00198-011-1703-1
|View full text |Cite
|
Sign up to set email alerts
|

Combination of texture analysis and bone mineral density improves the prediction of fracture load in human femurs

Abstract: In these excised femurs, the combination of bone texture parameters with BMD demonstrated a better performance in the failure load prediction than that of BMD alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 36 publications
(62 reference statements)
2
24
1
1
Order By: Relevance
“…21 The combination of texture parameters and BMD has been shown to improve the assessment of fracture risk compared to using texture parameters or BMD alone. 21,22 Combining morphological structure parameters and BMD demonstrates the highest correlations with bone strength. 23,24 Another study reported that individual cortical thickness and BMD showed better performance.…”
Section: A N U S C R I P Tmentioning
confidence: 95%
“…21 The combination of texture parameters and BMD has been shown to improve the assessment of fracture risk compared to using texture parameters or BMD alone. 21,22 Combining morphological structure parameters and BMD demonstrates the highest correlations with bone strength. 23,24 Another study reported that individual cortical thickness and BMD showed better performance.…”
Section: A N U S C R I P Tmentioning
confidence: 95%
“…Therefore, bone quality measures, including architecture, turnover, damage accumulation and mineralization, have been proposed as additional features in predicting bone fractures (NIH, 2000). New techniques, such as fractal texture analysis (Majumdar et al, 1993; Benhamou et al, 1994; Buckland-Wright et al, 1994; Majumdar et al, 2000; Pothuaud et al, 2000; Chappard et al, 2001; Messent et al, 2005; Apostol et al, 2006; Lespessailles et al, 2008; Le Corroller et al, 2012), topological analysis (Boehm et al, 2007; Boehm et al, 2008), hip structure analysis (Beck, 2003; Beck, 2007), finite element analysis (Langton et al, 2009), and trabecular bone score based on the experimental variogram (Pothuaud et al, 2008; Pothuaud et al, 2009; Hans et al, 2011; Winzenrieth et al, 2013), have been introduced to enhance the prediction of bone fractures from DXA images by providing additional information of bone quality.…”
Section: Introductionmentioning
confidence: 99%
“…Fractal analysis of texture in two-dimensional images is a useful imaging technique that has been successfully applied to high-resolution radiography images to extract the hidden geometric and microstructure parameters of trabecular bone in both clinical studies and in vitro studies (Majumdar et al, 1993; Benhamou et al, 1994; Buckland-Wright et al, 1994; Majumdar et al, 2000; Pothuaud et al, 2000; Chappard et al, 2001; Messent et al, 2005; Apostol et al, 2006; Lespessailles et al, 2008; Le Corroller et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…For example, DXA does not assess bone microarchitecture, which is included in the definition of osteoporosis and is an important contributor to bone strength and quality [2, 7, 8]. Indeed, the addition of structural measures to BMD improves the prediction of bone strength in ex vivo studies [911]. Second, DXA has poor sensitivity for the detection of patients with bone fragility.…”
Section: Introductionmentioning
confidence: 99%